Diagnosing rare diseases: A sociotechnical approach to the design of complex work systems. (July 2020) - Hay, Georgia J.; Klonek, Florian E.; Parker, Sharon K.
Abstract: How do complex healthcare systems that are organised into distinct speciality areas achieve effective patient care transitions when patients present with a rare constellation of symptoms that affect multiple body systems? How do these patients challenge existing ways of organising tasks, clinical activities, and interdependent responsibilities? The current study applies a sociotechnical systems perspective to understand how these complex work design and care-related challenges were resolved by the Western Australian Undiagnosed Diseases Program. We conducted a two-year longitudinal, qualitative study of this program, conceived to improve the diagnosis and management of patients with rare, multi-system disorders by piloting a re-design of the local system of diagnostic work. Specifically, we (1) compared the configuration and effectiveness of the old system and the re-designed system; and (2) analysed the process of system re-design (i.e., the design, implementation, and operation of the program) in order to understand the factors that contributed to – or inhibited – its success. We discuss the theoretical and practical implications of our findings for effectively re-designing complex, trans-organisational work systems. Highlights: Removing the need for patient care transitions is crucial for the effectiveness of some sociotechnical work systems. Creative, cross-disciplinary collaboration in healthcare relies heavily on the social components of the work system. Technology reduces information processing demands, but is not sufficient in-and-of-itself for highly complex work. Barriers, enablers, accelerators, and motivators need to be addressed in the redesign of trans-organisational work systems.